Occurrence, detection and removal of amoxicillin in wastewater: A review - Aryee, Aaron Albert; Han, Runping; Qu, Lingbo (Journal of cleaner production, 2022)
The widespread use of amoxicillin (AMX) has been attributed to its ability to treat some common diseases. Its presence in industrial and domestic sewage has been a source of concern in recent times owing to the risk and challenges it poses to the aquatic environment and to human health. In this regard, studies with the aim of investigating their concentration levels and/or employing some remediation techniques for their removal from wastewater have been reported. In this review, the ways by which amoxicillin enters the environment and their associated potential effects are discussed. Also, some discussions on the detection methods (such as chromatography and spectroscopy) and remediation techniques (such as adsorption technique, advanced oxidation processes and biological treatment) applied for their removal were also presented with the aim of presenting a holistic view on this subject. In a bid to understand the choice of a remediation technique, a brief overview of the method and its advantages are presented. From the studies sampled, it can be inferred that the advanced oxidation processes (AOP) and constructed wetlands have been the most and least applied methods for the remediation of AMX in wastewater due to the disparity in their associated efficiencies. The mineralization of AMX was in all cases less than the degradation efficiency of the remediation technique due to the stability of the products and/or intermediates formed from the degradation process as compared to AMX. The review ends by presenting research gaps and recommendations in addressing these challenges in a bid to inspire further studies on this subject.